(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Novriyanti N, Takandjandji M. 2022. Application of sexual dimorphism-derived variation in morphometrics and intraspecific interaction likelihood in Sunda pangolin (Manis javanica) to increase species encounter rates. Biodiversitas 23: 2753-2759. Effectively encounters opportunities of Sunda pangolin (Manis javanica) in natural habitats is still necessary to have more research. A diversity of pangolins’ physical and biological characteristics has been disclosed to facilitate the identification process in natural habitats. However, pangolins are animals that tend to be solitary; they have fast movement, so the area coverage is extensive; this condition complicates the data collection process. It is unknown yet, whether pangolins of different sexes usually exist in the same space and time, either in terms of foraging or other interactions, known as intra-specific interactions. Thus, this study aimed to predict intraspecific interactions of M. javanica to increase the encountering of pangolins chance in natural habitats. As many as 29 individual pangolins (14 males and 15 females) be measured its morphometric data. To convincingly justify that morphometric variation can be used as encounter rate opportunities in natural habitats, a series of analyses, i.e., univariate test, correlation analysis, and multiple regression, were applied to this research. Other estimations from feeding activity data were also carried out to detect pangolins’ niche width and its overlap according to sexual dimorphism. Univariate analysis shows that overall, the total body length (head to tail) of both males and females does not differ significantly. But, the correlation coefficient indicates the physical character of female and male body length is related to each other (value 0.769**). The resulting regression model indicates that the presence of pangolins in their sex similarity in a particular place tends to be avoided, while there is a 1:1 probability of sexual dimorphism. This also means that males and females can be used as the same individual in ecological observations.